1969
DOI: 10.1017/s0003356100026787
|View full text |Cite
|
Sign up to set email alerts
|

The effect of different dietary energy concentrations on the voluntary intake and growth of intensively-fed lambs

Abstract: In a comparative slaughter trial which covered growth from about 16 kg to 40 kg live weight, five groups of six Romney x Swaledale lambs were offered ad libitum five pelleted diets (A to E) in which rolled barley was gradually replaced by an 80 : 20 mixture of rolled oats : oat husks to the extent that the calculated metabolizable energy (ME) concentration fell from approximately 2-9 (A) to 2-5 (E) Mcal/kg DM. Although daily live-weight gains did not differ significantly between treatments, the daily carcass g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
10
0

Year Published

1971
1971
1990
1990

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 21 publications
(11 citation statements)
references
References 15 publications
(11 reference statements)
1
10
0
Order By: Relevance
“…As quoted above, Andrews et al (1969) showed that even the intake of oats can be physically restricted in early-weaned lambs weighing less than 40 kg. This is vividly illustrated in earlyweaned calves and lambs, where the rumen is insufficiently developed for the consumption of sufficient roughage for survival.…”
Section: I11b Rumen Volumementioning
confidence: 86%
See 1 more Smart Citation
“…As quoted above, Andrews et al (1969) showed that even the intake of oats can be physically restricted in early-weaned lambs weighing less than 40 kg. This is vividly illustrated in earlyweaned calves and lambs, where the rumen is insufficiently developed for the consumption of sufficient roughage for survival.…”
Section: I11b Rumen Volumementioning
confidence: 86%
“…Animals receiving poor-quality diets, which impose physical limitations to intake, also often consume more under such circumstances, as a result of metabolic From Andrews et al (1969). Animals receiving poor-quality diets, which impose physical limitations to intake, also often consume more under such circumstances, as a result of metabolic From Andrews et al (1969).…”
Section: )mentioning
confidence: 99%
“…Andrews et al (1969) found that weaned lambs used the ME of concentrates with an efficiency of 50% for growth. This paper describes an experiment designed to measure the efficiency of utilisation of lucerne by lambs weaned at 5 weeks of age.…”
Section: Introductionmentioning
confidence: 99%
“…It has been shown, furthermore, that inclusion of fibrous material such as oat husk in the barleybased diets reduced intake in the early stages of growth and that only after reaching about 35 kg live weight were the lambs capable of compensating, by consuming more, for the reduction in digestibility caused by including oat husk (Andrews, Kay and 0rskov, 1969). If, however, the oat husk was ground, lambs were able to achieve earlier compensation in intake (Owen, Davies and Ridgman, 1969;Andrews and 0rskov, 1970c).…”
Section: Introductionmentioning
confidence: 99%